Humanized Mice Are Instrumental to the Study of Plasmodium falciparum Infection - Tyagi, Rajeev K.; Tandel, Nikunj; Deshpande, Richa; Engelman, Robert W.; Patel, Satish D.; Tyagi, Priyanka (Frontiers in Immunology, 2018)
Research using humanized mice has contributed to advancements in our understanding of human haematopoiesis, non-adaptive and adaptive immunity, autoimmunity, infectious disease, cancer biology, and regenerative medicine. Challenges posed by the human malaria parasite Plasmodium facliparum include its complex life cycle, the evolution of drug resistance against anti-malarials, poor diagnosis, and a lack of effective vaccines. Advancements in genetically engineered and immunodeficient mouse strains have allowed studies of its asexual blood stage, exoerythrocytic stage, and its transition from liver-to-blood stage infection in a one vertebrate host. The present review discusses the process of “humanization” of various immunodeficient/transgenic strains and their contribution to translational biomedical research. This paper also reviews the strategies employed to overcome the remaining limitations of developed human-mouse chimeras.